Adaptation of Migrant Children in a Multicultural Educational Environment in Conditions of the Municipal Experimental Platform - Elena I. Mychko; Anna B. Serykh; Elena V. Potmenskaya (ARPHA Proceedings, 2020)
The adaptation of migrant children in a multicultural learning environment requires taking new roles in an unfamiliar sociocultural situation. An educational institution must create a psychological atmosphere of mutual respect between children as well as between pupils and teachers, based on positive motivation to develop multicultural competencies.The problem addressed in this study, namely the need for the successful adaptation of migrant children to a multicultural learning environment helps to define its aim. The research seeks to demonstrate the efficiency of the municipal experimental platform model in the adaptation of migrant children at a multicultural school.To test the hypothesis that a municipal experimental platform can be instrumental in the adaptation of migrant children, three groups of methods were used. Theoretical methods included the analysis of psychological and pedagogical literature on migration pedagogy as well as the study and identification of best pedagogical practices for modelling a learning environment. Empirical methods comprised observations, surveys of teachers and parents, and interviews with parents. The third group consisted of mathematical data-processing methods.Monitoring looked into how the experimental platform model was introduced into schools in the city of Kaliningrad. To that end, the rate of multicultural competency of multicultural schoolteachers was calculated. The parents of migrant children were surveyed to assess how favourable school environment was. Children’s satisfaction with interpersonal relationships, their attitude to school, and academic performance in younger schoolchildren were measured.The results obtained may benefits specialists in educational management as well as experts working with migrant children.